A new ESIPT-based fluorescent probe for highly selective and sensitive detection of HClO in aqueous solution. Issue 13 (29th March 2017) - Pan, Yimin; huang, Jing; Han, Yifeng
Graphical abstract: Highlights: A new ESIPT-based fluorescent probe for the detection of HClO has been developed. The probe shows high selectivity and sensitivity for HClO in aqueous solution. The detection limit of probe for HClO is 13.2 nM. Abstract: A new ESIPT-based fluorescent probe, PHC2, for the detection of hypochlorous acid has been rationally designed and developed. Endowed by the specific reaction between hypochlorous acid and phenyl azo group, PHC2 features high degree of selectivity and sensitivity for HClO with a low detection limit (13.2 nM) under physiological conditions in neutral aqueous solution.